Occurrence, growth and survival of yeasts in matured cheddar - Laubscher, Petrus Johannes (University of the Free State, 1999)
Yeasts play an important role in dairy products causing spoilage or contribute positively to the ripening of some cheeses due to their lipolytic and proteolytic activities and the ability to grow at low temperatures, pH and water activity, and high salt concentrations. Despite various factors affecting the survival and growth of yeasts in cheese, the food commodity is considered as a potential habitat of yeasts. Cheese renders an ideal medium for the survival and progression of yeasts due to the availability of the necessary nutrients. A historical review of the incidence of yeasts, their interaction with bacteria and their properties, during the manufacturing and ripening of matured Cheddar cheese is given in Chapter 1. The history of Cheddar cheese making, the fermentation of milk during cheese making, different starter cultures and methods of application and occurrence of yeasts are highlighted. In Chapter 2 a survey was undertaken with the objective of identifying the predominant yeast contaminants associated with matured Cheddar cheese production. A total of 168 yeasts strains, representing 12 different species, isolated from matured Cheddar cheese and the immediate environment were isolated. Once the identity of the yeast flora associated with the cheese had been established, the survey was extended to determine the sources of yeast infection during the processing of the matured Cheddar cheese. The results obtained, showed that yeasts contributed substantially to the deterioration as well as the ripening of the matured cheese, especially when stored under environmental conditions exhibiting, low temperature, water activity and pH values and high salt concentrations. In Chapter 3 seven of the most dominant yeasts frequently associated with dairy products are screened for their resistance against nine commercial cleaning compounds and sanitizers commonly used in the dairy industry. None of the compounds used, however, were able to sufficiently kill the yeasts, within 60 minutes. In Chapter 4 the influence of temperature and NaCI on the dominant yeasts isolated in a cheese factory, during the manufacturing and ripening of matured Cheddar cheese was examined. Relevant yeast species were screened for lipolytic and proteolytic activities, and their ability to ferment lactose. The chemical and physical characterition including pH, fat content, water activity, salt and moisture were determined and its relevance to the growth and survival of yeasts studied. The interaction between yeasts, coliforms and total bacteria during the manufacturing and ripening of matured Cheddar cheese, by using DVI- and Mass- starters was studied in Chapter 5. Results obtained indicate that yeast contaminants have to be controlled during the salting process to prevent overgrowth of the starter cultures. During the salting stage, the curd is prone to yeast contamination and may result in excessive loads due to the competitive growth advantage of the species and the simultaneous bacterial inhibition. This may contribute to product spoilage or stimulate the growth of the starters adding to the formation of aroma components.
Keywords: Diary processing; Yeast; Food spoilage; Food -- Microbiology; Dissertation (M.Sc. (Microbiology and Biochemistry))--University of the Free State, 1999